2019
DOI: 10.1186/s12913-019-4593-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding corporate governance of healthcare quality: a comparative case study of eight Australian public hospitals

Abstract: BackgroundPatients are sometimes harmed in the course of receiving hospital care. Existing research has highlighted a positive association between board engagement in healthcare quality activities and healthcare outcomes. However, most research has been undertaken through surveys examining board engagement in a limited number of governance processes. This paper presents evidence of a comprehensive range of processes related to governing healthcare quality undertaken at the corporate governance level. This prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 52 publications
0
26
0
2
Order By: Relevance
“…In this scenario, health councils and hospital leaders from the international community warn of the awareness of risks and responsibilities in assuming attitudinal changes in management leadership that clearly impact the quality and safety of work (2) . Studies recommend and request hospital managers to take responsibility for management results and quality care (2)(3) . Setting priorities and disseminating strategic goals is directly related to high hospital performance, the core of hospital management (3) .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this scenario, health councils and hospital leaders from the international community warn of the awareness of risks and responsibilities in assuming attitudinal changes in management leadership that clearly impact the quality and safety of work (2) . Studies recommend and request hospital managers to take responsibility for management results and quality care (2)(3) . Setting priorities and disseminating strategic goals is directly related to high hospital performance, the core of hospital management (3) .…”
Section: Introductionmentioning
confidence: 99%
“…Studies recommend and request hospital managers to take responsibility for management results and quality care (2)(3) . Setting priorities and disseminating strategic goals is directly related to high hospital performance, the core of hospital management (3) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In South Africa, the board members tend to forget their responsibility on the health care system because most of them are a politician and fail to perform what the community needs in the health care quality systems. 6 In Ethiopia, the study showed that the lack of commitment of board members to meet regularly and to attend meetings with motivations was insufficient. In some cases, board members' were over devoted to more than one board and members were too busy to arrange their governing board tasks.…”
Section: Introductionmentioning
confidence: 99%